Administrative Strategies For Effective Teaching In Basic Education In The Era Of Frozen Moment In Rivers State, Nigeria - Ukala, Chinyere Catherine (Advances in Social Sciences Research Journal, 2020)
The study explored administrative strategies for effective teaching in basic schools in the era of frozen moment in Rivers State, Nigeria. Three research questions were answered while three hypotheses were tested. The study adopted an analytic survey research design with a population of 247 headteachers in 247 public basic schools in Rivers State. The sample size is 172 headteachers representing 70% of the population of the headteachers. The sample size was arrived at using proportionate stratified random sampling technique. An instrument titled Administrative Strategies for Effective Teaching Scale (ASETS) was used for data collection. Face and content validities were ensured by experts in Educational Management as well as Test and Measurement in the University of Port Harcourt. The internal consistency reliability coefficient of 0.83 was computed for ASETS through Cronbach alpha statistical method. Mean and standard deviation were used to answer the research questions while z-test was used to test the hypotheses at 0.05 level of significance. It was found that the headteachers can use reward management system as well as online supervision of their teachers’ academic preparation progress to enhance their teaching effectiveness. It was also found that the headteachers have the problem of time management and financial incapacity to carry out online administrative functions. It was recommended among others that the headteachers and local and state governments should assist the teachers in procuring electronic gadgets by giving them soft loans. The headteachers should cultivate the attitude of making use of online platform to disseminate information to the teachers for teaching effectiveness.